SENTUHAN BORDIR PADA BUSANA PERPISAHAN REMAJA PUTRI BERGAYA 1960-AN - Rika Nurnaningsih (Akademi Seni dan Desain Indonesia Surakarta, 2012)
Fashion design in this thesis aims to design a prom dress style girls the 1960s. Its main ingredient is combined with Shimmer Taffeta fabric Lurik Indonesia as part of its tradition. Making prom dress was inspired by starfish taken the elements of color and shape. To obtain a form from the sea star by using embroidery techniques.Embroidery technique used is to stack the various colors of yarn. The color of the yarn used ranging from dark to light color, then embroidered using embroidery machines to reach 6-10 layers. Embroidery is cleaved from the middle and produce the color resembles the color of the sea star.This prom dress is composed of three works, the pieces form one long party dresses above the knee for teens. Design I, with a piece strapless gown, was given later in the neck strap with embroidery and decorative pieces opnaisel at the waist. Design II, one model of party dresses shoulders or one shoulder with the pieces of the wave in flounces which give accent on the stack, which is associated as a supporting element in the idea that the form of kelp or seaweed. Design III, a party dress at the waist with asymmetrical cuts and circular flounces opnaisel in place on the neck of this dress adds a unique look and attractive.